A cluster and its trajectory: evidence from the history of the French Champagne production cluster. (14th March 2016) - Leszczyńska, D.
Abstract: This article explores historical and contemporary evolutions within the French Champagne cluster. Its purpose is to demonstrate how the study of rural dynamics in the knowledge economy could be improved through an analysis of its history. Our theoretical contribution includes an analysis of the French Champagne cluster's trajectory with the aim of illustrating the perspectives of human capital and knowledge-based cluster theory. A narrative historical methodology was carried out within a mature cluster. The paper empirically relates the labour and workforce history of Champagne from the twelfth century onwards in order to show the role of the local entrepreneurial context in the cluster's longitudinal development. The evolutionary dynamics of the champagne-producing cluster can be understood through the lens of four historical sequences: an institutional sequence, a technological sequence, an industrialisation sequence and a territorial sequence. The cluster's recent development highlights the increasing importance of a creative class that followed the demographic reversal within its specific rural area.